2004
DOI: 10.1242/jcs.01156
|View full text |Cite
|
Sign up to set email alerts
|

A NHERF binding site links the βPDGFR to the cytoskeleton and regulates cell spreading and migration

Abstract: The Na+/H+ exchanger regulatory factor, NHERF, is a multifunctional adapter protein involved in a wide range of physiological activities. NHERF associates with merlin and the ezrin/radixin/moesin (MERM) family of membrane-actin cytoskeletal linker proteins through its C-terminus and is capable of interacting via its PDZ1 domain to the βPDGF receptor (βPDGFR). Thus, NHERF, potentially links the βPDGFR to the actin cytoskeleton through its interaction with MERM proteins. In the present study, we have examined wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 49 publications
5
52
0
Order By: Relevance
“…Our findings indicate that merlin overexpression leads to disruption of FAK binding to its interacting partners Src and p85. The inhibitory effect of merlin on FAK activity could be either direct, as merlin has been previously shown to form a complex with FAK and NHERF (James et al, 2004), or indirect through inhibition of Rac/PAK signaling, which is known to cross-talk with FAK signaling (Hsia et al, 2003;Brown et al, 2005;Mitra et al, 2005). Indeed, we and others have previously linked merlin to Rac/PAK signaling, as PAK was found to be able to phosphorylate and inactivate merlin (Kissil et al, 2002;Xiao et al, 2002) and unphosphorylated merlin has been shown to inhibit PAK activity (Kissil et al, 2003;Hirokawa et al, 2004;Xiao et al, 2005) and Rac translocation to matrix adhesions (Okada et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings indicate that merlin overexpression leads to disruption of FAK binding to its interacting partners Src and p85. The inhibitory effect of merlin on FAK activity could be either direct, as merlin has been previously shown to form a complex with FAK and NHERF (James et al, 2004), or indirect through inhibition of Rac/PAK signaling, which is known to cross-talk with FAK signaling (Hsia et al, 2003;Brown et al, 2005;Mitra et al, 2005). Indeed, we and others have previously linked merlin to Rac/PAK signaling, as PAK was found to be able to phosphorylate and inactivate merlin (Kissil et al, 2002;Xiao et al, 2002) and unphosphorylated merlin has been shown to inhibit PAK activity (Kissil et al, 2003;Hirokawa et al, 2004;Xiao et al, 2005) and Rac translocation to matrix adhesions (Okada et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…FAK expression and/or activity are reported to be upregulated in a wide range of malignancies, including cancers of the thyroid, prostate, cervix, colon, rectum, oral epithelium, ovary and breast (McLean et al, 2005;Watermann et al, 2005). Ezrin, another member of the ERM family, has been shown to positively regulate FAK activity (Poullet et al, 2001), and merlin itself has been proposed to form a complex with FAK and the Na þ /H þ exchanger regulatory factor, NHERF (James et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…PDGFR interaction with integrins helps localizing PDGFRs and interacting molecules at focal adhesions, which are sites where several signaling pathways initiate and cross-talk (Clark and Brugge 1995). Recently, Na + / H + exchanger regulatory factors (NHERFs) were shown to bind PDGFR-␤ and link it with focal adherence kinase and the cortical actin cytoskeleton (James et al 2004), as well as to N-cadherin (Theisen et al 2007) and the phosphatase PTEN ( Fig. 4; Takahashi et al 2006).…”
Section: Pdgfr-induced Signaling Pathwaysmentioning
confidence: 99%
“…For a comprehensive overview on the signalling pathways through which PDGF-BB elicits downstream cascades, refer to previous reviews on the topic (Andrae et al, 2008;Heldin and Westermark, 1999;Tallquist and Kazlauskas, 2004). PDGFR can also interact with integrins, through the Na + /H + exchanger regulatory factors (NHERFs) that link it to focal adhesion kinase and cytoskeleton (James et al, 2004;Veevers-Lowe et al, 2011). In turn, PDGFRs can be also affected by the ECM components (DeMali et al, 1999;Veevers-Lowe et al, 2011).…”
Section: Pdgf-bb Is Predominantly Expressed During Tendon Healingmentioning
confidence: 99%